An Analysis of Character Education in Enhancing the Responsibility Attitudes of Eighth-Grade SIS Aljufri Students at SMP Negeri 2 Dampal Selatan - Erni Nurdin; Meli; Sitti Hawaena; Moh Jusri Kahar; Nuratika (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This research aims to examine the implementation of character education in an effort to improve the sense of responsibility among eighth-grade students at SIS Aljufri SMP Negeri 2 Dampal Selatan. This research was motivated by the discovery of various student behaviors that reflect low attitudes of responsibility, including tardiness in attending classes, lack of discipline in completing assignments, and minimal concern for school cleanliness and order. The approach used in this research is descriptive qualitative with a case study type of research. Data collections were carried out through observation, interviews, and documentation techniques, with the research subjects consisting of teachers and students of class VIII SIS Aljufri. The results of the research showed that character education at SMP Negeri 2 Dampal Selatan has been implemented through the integration of character values in learning activities, the cultivation of positive attitudes in the school environment, the example set by teachers, and the enforcement of school rules. The responsibility attitude of students has generally improved, particularly in the performance of tasks and participation in the learning process, although there are still some students who need continuous guidance. Factors supporting the improvement in responsibility attitude include the role of teachers as role models, the support of the school environment, and the existence of strict rules and sanctions. The inhibiting factors include differences in student character, limited learning time, and the influence of the environment outside of school. Therefore, character education has a strategic role in shaping students' attitudes of responsibility when it is implemented consistently and continuously.